Memory discrimination is promoted by the expression of the transcription repressor WT1 in the dentate gyrus - Munari, Leonardo; Patel, Vishwendra; Johnson, Nicholas; Mariottini, Chiara; Prabha, Som; Blitzer, Robert D.; Iyengar, Ravi (Frontiers in Behavioral Neuroscience, 2023)
The hippocampus is critical for the precise formation of contextual memories. Overlapping inputs coming from the entorhinal cortex are processed by the trisynaptic pathway to form distinct memories. Disruption in any step of the circuit flow can lead to a lack of memory precision, and to memory interference. We have identified the transcriptional repressor Wilm's Tumor 1 (WT1) as an important regulator of synaptic plasticity involved in memory discrimination in the hippocampus. In male mice, using viral and transgenic approaches, we showed that WT1 deletion in granule cells of the dentate gyrus (DG) disrupts memory discrimination. With electrophysiological methods, we then identified changes in granule cells' excitability and DG synaptic transmission indicating that WT1 knockdown in DG granule cells disrupts the inhibitory feedforward input from mossy fibers to CA3 by decreasing mIPSCs and shifting the normal excitatory/inhibitory (E/I) balance in the DGàCA3 circuit in favor of excitation. Finally, using a chemogenetic approach, we established a causal link between granule cell hyperexcitability and memory discrimination impairments. Our results suggest that WT1 enables a circuit-level computation that drives pattern discrimination behavior.To prevent interference between memories that share similar features, the brain needs to store distinct electrical activity patterns. This ability critically depends on the hippocampus, and it is mediated by a process called pattern separation which is still poorly understood. WT1's function in normal brain physiology and memory is still unknown. Our new findings support a critical role for WT1 in normal brain physiology and cognition and provide new information on WT1 effects in the dentate gyrus, and its role in modulating discrimination between similar events that occur close in time. Our results demonstrate the importance of cell-level changes in modulating intercellular functions to control organismal behavior -in this case, memory precision.